Perancangan prototype UI/UX aplikasi home service kendaraan berbasis mobile dengan pendekatan Design Thinking - Nalendra, Indra Putra; Swalaganata, Galandaru (Universitas Merdeka Malang, 2024)
Vehicle repair services require most customers to spend extra time visiting a repair shop. Customers generally also have to wait in line for a very long time, so that service becomes less effective and efficient. This research aims to design a UI/UX prototype of the mobile-based Hi Service application so that it is hoped that it can make it easier to manage call services or home service for vehicle repairs by directly visiting the customer's home. The research method used is the Design Thinking approach which has five process stages in meeting user needs. UI/UX prototype testing is carried out using usability testing with a System Usability Scale (SUS) assessment. The research results show that the Hi Service application prototype test received a score of 82 and was included in the excellent category or rate. The study shows that the Design Thinking approach to the prototype created is able to meet user needs. Apart from that, testing the prototype through usability testing with SUS assessment showed a positive impact on the user experience when running the UI/UX prototype of the Hi Service application.